Economic and social determinants of carbon emissions: Evidence from organization of petroleum exporting countries. Issue 3 (27th February 2020) - Coskuner, Cagay; Paskeh, Mersedeh K.; Olasehinde‐Williams, Godwin; Akadiri, Seyi S.
Abstract : This research investigates the economic and social determinants of carbon emissions in the Organization of Petroleum Exporting Countries (OPEC) over the period 1995–2016. The study particularly examines the link between CO2 emissions and four socio‐economic variables (per‐capita GDP, urbanisation, fossil fuel energy consumption and international trade). A long‐run relationship amongst these variables is confirmed by Kao, Pedroni and Johansen panel cointegration tests. Fully modified ordinary least squares outcomes show that the relationship between CO2 emission and GDP is non‐linear in OPEC countries and follows the inverted U‐shape suggested by the environmental Kuznets curve hypothesis. Also, urbanisation is responsible for a significant proportion of carbon emissions in OPEC countries. As expected, fossil fuel energy consumption is a significant positive driver of carbon emission. International trade significantly contributes to carbon emissions within OPEC member countries.